The Quantose Insulin Resistance Test for Maternal Insulin Resistance: A Pilot Study - Eid, Joe; Kechichian, Talar; Benavides, Elisa; Thibodeaux, Lisa; Salazar, Ashley E.; Saade, George R.; Saad, Antonio F. (American Journal of Perinatology, 2020)
Objective Insulin resistance (IR) increases during pregnancy which can lead to hyperinsulinemia, gestational diabetes mellitus (GDM), and neonatal hypoglycemia (NH), especially in obese women. Glucose tolerance testing (GTT) is used clinically to evaluate IR in pregnancy. Quantose IR score index is a novel blood screen of IR validated in nonpregnant individuals. The score is generated using an algorithm that combines insulin and three biomarkers of fatty acid pathways (α-hydroxybutyrate, oleic acid, linoleoyl-glycerophospocholine). Our objective was to determine the validity of Quantose IR test (Metabolan Inc. Morrisville, NC) in assessing IR in pregnant obese women, as compared with the homeostatic model assessment of insulin resistance (HOMA-IR), and its ability to predict GDM and NH.Study Design Women between 100/7 and 136/7 weeks of gestation with a pre-pregnancy or early pregnancy body mass index more than 30 kg/m2, and no pregestational diabetes, were included. Fasting blood samples were collected at 100/7 to 136/7 (T1) and 240/7 to 280/7 (T2) weeks. Quantose IR and HOMA-IR were calculated. All women underwent an early (T1; indicated for women with obesity) and a T2 glucose tolerance tests. GDM was diagnosed using the two-step approach, and NH was defined as a neonatal glucose less than 40 mg/dL in the first 24 hours of life. Linear regression and receiver operating characteristic curves were used for analysis.Results The trial enrolled 100 patients. Ten subjects (10%) were diagnosed with GDM in the second trimester and none in the first trimester. At T1, Quantose IR (R2 = 0.48), but not 1-hour glucose tolerance test (R2 = 0.07), correlated with HOMA-IR. Similar correlations were observed at T2. The 1-hour glucose tolerance test followed by HOMA-IR and Quantose IR (area under the curve [AUC]: 0.82, 0.68, and 0.62, respectively) were predictors of GDM. Quantose IR (AUC: 0.74) and 1-hour glucose tolerance test (AUC: 0.72) at T1 and T2 (AUC: 0.75; AUC: 0.93; respectively) were best predictors of NH. The best cut offs, sensitivities, and specificities for prediction of NH were determined.Conclusion Similar to nonpregnant individuals, Quantose IR appears to be a valid measure of IR in obese pregnant women. First trimester Quantose IR is a predictor of GDM diagnosed in the second trimester and NH. Given that it requires a single blood draw and no glucose challenge, it may be a useful test to evaluate and monitor IR in pregnancy. Our findings may be used as pilot data to explore the potential use of Quantose IR in pregnancy further.Key Points
Keywords: insulin resistance; Quantose IR; gestational diabetes; neonatal hypoglycemia